Insulin Resistance and Dietary Management Strategies in Gestational Diabetes - Zeng , Yi; Pan, Honggui (South Eastern European Journal of Public Health, 2024)
Gestational diabetes is a common complication of pregnancy, and the relationship between insulin resistance and dietary management strategies has always been a hot topic of research. This article uses controlled experiments to further explore the mechanism of insulin resistance in patients with gestational diabetes and the impact of dietary management strategies on its treatment. It can be seen from experimental data that dietary management strategies play a very important role in the treatment of patients with gestational diabetes. Research and data show that reasonable dietary control can effectively control blood sugar levels in patients with gestational diabetes and reduce the possibility of fetal complications. And according to the individual differences of patients, customized individualized dietary management strategies can improve the treatment effect. However, in-depth research is still needed to improve the prevention and treatment of gestational diabetes to reduce the impact of gestational diabetes on mothers and babies.